Internal Control and Accounting Conservatism: The Role of Managerial Ability Moderators - Zainal Asyiqin; Bawono, Andy Dwi Bayu; Zulfikar (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Objective: This research seeks to evaluate the impact of internal control on accounting conservatism while also analyzing managerial ability fuctions as a moderating variabel. Methodology/approach: The research adopts a quantitative approach by utilizing financial statement data from manufacturing companies listed on the indonesia Stock Exchange (IDX) over the 2018-2023. The sampel was detemined using purposive sampling, yielding 124 companies each year and the anaysis was conducted with Eviews. Findings: The study’s finding demonstrate that internal control and managerial ability influence accounting conservatism. However, managerial ability weakens the moderating effect, suggesting that higher managerial ability can substitute for internal control in influencing the level of accounting conservatism. Practical implications: Previous research has generally examined determinants of accounting conservatism in isolation, such as internal control or managerial characteristics. However, managerial ability as a moderation variable in the link between internal control and accounting conservatism is still rarely explored, thus opening up space for this study. Originality/value: Novelty of study lies in the testing of managerial ability a moderation variable that is able to strengthen or weaken the influence of internal control in accounting conservatism.